The Effect of Superior Intervention, Ethics, and External Disturbances on Auditor Independence - Ricky Bryan D.P. Tampubolon (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
This study aims to examine the effect of superior intervention, ethics, and external disturbances on auditor independence, both partially and simultaneously. Using a quantitative approach with multiple linear regression, data were collected from 151 internal and external auditors in Jakarta with a minimum of two years of work experience through a questionnaire. The analysis results show that superior intervention has a significant negative effect on auditor independence, indicating that pressure or restrictions from management can reduce professional autonomy. Ethics were found to have a significant positive effect, meaning that the internalization of moral and professional values can strengthen auditors’ objectivity and resistance to external pressures. Meanwhile, external disturbances have a significant negative effect, suggesting that factors beyond the auditor’s control, such as resource limitations and restricted access to information, can undermine the quality of judgment and the auditor’s independent stance. Simultaneously, these three variables significantly affect independence, explaining 23.9% of the variation in auditor independence. These findings highlight the importance of control strategies to minimize management intervention, enhance continuous ethics education, and manage the risks of external disturbances to safeguard the integrity of the audit process. This study provides practical implications for audit organizations and regulators to strengthen policies, ethical culture, and adequate resource support so that auditor independence is maintained in order to achieve reliable and credible financial statements.